PENGARUH VARIASI DESAIN SUDU TERHADAP KARAKTERISTIK HIDRODINAMIKA TURBIN AKSIAL VORTEX ULTRA LOW HEAD MENGGUNAKAN METODE CFD - Khanif, Masnurojak Bin; Rahman Saleh, Arif; Fajarningrum, Nurmala Dyah; Sulistiyo, Raka Mahendra (ELEMEN : JURNAL TEKNIK MESIN, 2024)
Renewable energy is being developed by many advanced countries due to its positive impacts. Indonesia has a high potential for hydropower generation using axial vortex turbines, which are effective at low head heights. Researchers use experimental methods, employing CFD simulations with specific boundary conditions. In one blade variation, testing was conducted 18 times with speed variables (20, 40, 60, 80, 100, 120 RPM) and blade angles of 22.5°, 35°, 40°. Torque data was collected after achieving convergence. The results showed the highest torque at 22.5° blade angle and 80 RPM speed, amounting to 2.4 N.m, and efficiency of 57.90% at 120 RPM. Researchers concluded that the decrease in torque is caused by the increase in vortex flow, reducing interaction between the blade and fluid after 80 RPM, while the increase in torque before 80 RPM is due to minimal swirling in the basin.